2015 48th Hawaii International Conference on System Sciences 2015
DOI: 10.1109/hicss.2015.601
|View full text |Cite
|
Sign up to set email alerts
|

Do Daily Scrums Have to Take Place Each Day? A Case Study of Customized Scrum Principles at an E-commerce Company

Abstract: Agile development approaches, such as Scrum, continue to gain importance in today's world. Since previous research has predominantly treated development approaches as a black box, we answer the call for empirical research concerning adoption of agile methods. The study's aim is to assess the adoption or adaption of Scrum principles at an e-commerce company. The findings of our in-depth single case study reveal that not all Scrum principles are suitable in each context. By discussing the reasons for adopting or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 25 publications
0
4
0
1
Order By: Relevance
“…For instance, time pressure that resulted from external decisions to change the size of the Development Team, introduce new requirements during a Sprint, or determine deadlines in advance contrast the roles, events, artifacts, and rules defined in the Scrum Guide. While previous research has shown the benefits of customizing agile methods [11,29], we contribute to a better understanding of customizing agile methods by revealing that -while customizing methods might be a necessity to fit prevailing organizational structures -the changes applied to the frameworks can also lead to negative effects (i.e., time pressure and related consequence in our context).…”
Section: Theoretical Contributionsmentioning
confidence: 82%
“…For instance, time pressure that resulted from external decisions to change the size of the Development Team, introduce new requirements during a Sprint, or determine deadlines in advance contrast the roles, events, artifacts, and rules defined in the Scrum Guide. While previous research has shown the benefits of customizing agile methods [11,29], we contribute to a better understanding of customizing agile methods by revealing that -while customizing methods might be a necessity to fit prevailing organizational structures -the changes applied to the frameworks can also lead to negative effects (i.e., time pressure and related consequence in our context).…”
Section: Theoretical Contributionsmentioning
confidence: 82%
“…20 However, these retrospectives are generally seen as extra workload in organizations. 62 Therefore, sprint retrospective meeting is omitted and the activities from this meeting are integrated into the sprint review meeting, 64 which is conducted at the end of a 4-week sprint. This is intended to make it so that the activities related to the sprint retrospective will be seen as indispensable in the Scrum team so that the team can be more productive.…”
Section: Scrum Meetingsmentioning
confidence: 99%
“…The authors presented an in-depth single case study, which in turn revealed that not all scrum principles are suitable in each context [51].…”
Section: Scrummentioning
confidence: 99%